Managing Heritage Language Development: Opportunities and Challenges for Chinese, Italian and Pakistani Urdu-Speaking Families in the UK - Curdt-Christiansen, Xiao Lan; La Morgia, Francesca (Multilingua, 2018)
Drawing on theories of family language policy and literacy environment, this inquiry explores and describes how family language policy is managed through literacy resources and literacy related activities in transnational families in the UK. A total of 66 families, each with at least one child between the age of 2 and 8, participated in this study. All children spoke English alongside their heritage/home language (HL), either Chinese, Italian, or Urdu. Data sources include: (a) a questionnaire about the children's general background and the parents' socio-economic and cultural capital and language practice in English and HL; (b) literacy resources and activities in both HL and English; (c) interview with parents. The results of this study show some interesting differences among Italian, Urdu and Chinese speakers, not only in their family language practices, but also in their attitudes towards mother tongue literacy and application of literacy practices in the home language. Although parental language management efforts were motivated by their aspirations to enrich their children's language repertoires, the different degrees of variation in family language input indicate that sociocultural and socio-political realities present difficulties and constraints that prevent families from developing literacy in the home language.